Experience with the implementation of central venous catheters by medical oncologists in a non-surgical setting - Alfonso Revuelta; Luka Mihic; Alfredo Castillo; Axel Mariño; Lucía Mateos; Claudia Iglesias; Carmen Sáenz de Jubera; Cristina Fernández; David Rodríguez-Rubí; Paula Jiménez-Fonseca; José Pablo Berros; Emilio Esteban (Scientific Reports)
Abstract Totally implantable central venous catheters (CVCs) are widely used in the management of patients with malignant diseases. Conventionally, port implantations were carried out by general surgeons and vascular radiologists. In recent years, the medical staff of the Medical Oncology department at the Central University Hospital of Asturias (HUCA) has developed a simplified methodology for the routine implantation of these devices. The aim of this study was to review our experience of CVCs and analyze the outcomes regarding catheter duration, complications, and cost comparison with respect to conventional port implantation by vascular radiologists. An observational epidemiological study was conducted, analyzing the methodology performed in a non-surgical, outpatient setting utilizing the Seldinger technique, without fluoroscopic control. A thorax X-ray was performed after each procedure and no prophylactic antibiotics were required. From January 2015 to March 2019, five hundred port systems were implanted, with a median age of 62 years (range 18–81), male 286/female 214. Most patients had a digestive tumor (79.4%). The right jugular vein was the most accessed in 345 patients (69%), followed by right subclavian in 144 (29%). Complications were observed in 49 patients (9.8%), immediate in 16 (3.2%), and late in 33 (6.6%). Thirty-nine devices were removed (7.8%). The cost incurred for port implantations by medical oncologists was lower (994.38 € cheaper for each device) compared to those implanted by vascular radiologists. Our experience suggests that implantation of port devices by medical oncologist in a non-surgical environment is safe and cost saving regarding conventional procedures.